The founder's mentality : how to overcome the predictable crises of growth - Zook, Chris, 1951-; Allen, James, 1960- (Boston, Massachusetts : Harvard Business Review Press, 2016)
"Why is profitable growth so hard to achieve and sustain? Most executives manage their companies as if the solution to that problem lies in the external environment-find an attractive market, formulate the right strategy, win new customers. But when Bain & Company's Chris Zook and James Allen, authors of the bestselling Profit from the Core, researched this question, they found that 90 percent of the challenges to growth are internal: increasing distance from the front lines, loss of accountability, and proliferating processes and bureaucracy, to name only a few. More crucial is their finding that companies experience a set of predictable internal crises, at predictable stages, as they grow; and that for even the healthiest companies, these crises, if not managed properly, can stifle the company's ability to grow further-and actively lead it into decline. The key insight from Zook and Allen's research is that managing these choke points requires a "founder's mentality"-an insurgent's clear mission and purpose, an unambiguous owner mindset, and a relentless obsession with the front line (behaviors typically embodied by a bold, ambitious founder)-to restore the speed, focus, and connection to customers, all of which are lost as companies grow. Based on the authors' decade-long study of companies in more than forty countries, any leader-not only a founder-can use a founder's mentality to overcome these predictable challenges and set their companies back on a path of sustainable growth. This book shows how, empowering leaders everywhere to control the destiny of their companies. "--
"Why is profitable growth so hard to achieve and sustain? Most executives manage their companies as if the solution to that problem lies in the external environment--find an attractive market, formulate the right strategy, win new customers. But when Bain & Company's Chris Zook and James Allen, authors of the bestselling Profit from the Core, researched this question, they found that 90 percent of the challenges to growth are internal: increasing distance from the front lines, loss of accountability, and proliferating processes and bureaucracy, to name only a few. More crucial is their finding that companies experience a set of predictable internal crises, at predictable stages, as they grow; and that for even the healthiest companies, these crises, if not managed properly, can stifle the company's ability to grow further--and actively lead it into decline. The key insight from Zook and Allen's research is that managing these choke points requires a "founder's mentality"--an insurgent's clear mission and purpose, an unambiguous owner mindset, and a relentless obsession with the front line (behaviors typically embodied by a bold, ambitious founder)--to restore the speed, focus, and connection to customers, all of which are lost as companies grow. Based on the authors' decade-long study of companies in more than forty countries, any leader--not only a founder--can use a founder's mentality to overcome these predictable challenges and set their companies back on a path of sustainable growth. This book shows how, empowering leaders everywhere to control the destiny of their companies"--
Keywords: Corporations - Growth; Industrial management; Corporate profits; Strategic planning; Leadership; BUSINESS & ECONOMICS - Strategic Planning; BUSINESS & ECONOMICS - Management; BUSINESS & ECONOMICS - Leadership